Statistical inferences of competing risks generalized half-logistic lifetime populations in presence of generalized type-I hybrid censoring scheme - Abdulaziz S. Alghamdi (Alexandria Engineering Journal, 2023)
The reliability analysis is usually concerned with failures in the time domain which show the difference between the quality control and reliability engineering. Also, It is very common in engineering or biological science units are falling under different causes of failure, which is known by competing risks model. In this paper, we have adopted the competing risks model when the lifetime of units distributed with generalized half-logistic (GHL) distribution. This model is formulated under consideration the failure done with two independent causes of failure. Also, to balance in statistical inference between the minimum number of failure and ideal test time, we are using, the type-I generalized hybrid censoring scheme (GHCS). The model parameters are estimated by maximum likelihood (ML) and Bayes approaches. The approximate confidence intervals, bootstrap confidence intervals and credible intervals are constructed. The developed results are discussed and assessed through Monte Carlo simulation study. A real data set is used and analyzed to report and illustrate the developed results.